Helping Couples in the Shadow of COVID‐19. Issue 3 (10th July 2020) - Stanley, Scott M.; Markman, Howard J.
Abstract : The pandemic caused by the SARS‐CoV‐2 virus (coronavirus) and the associated illness, COVID‐19, has caused a level of worldwide upheaval unlike any most people now living have seen in their lifetimes. This crisis affects people in their most important, committed, and intimate relationships. Although this crisis has damaged the health and well‐being of individuals, crushed economies, and led to an extensive period of uncertainty about the future, there may also be positive outcomes in the motivation people have to protect their relationships. In this paper, we focus on strategies that therapists and relationship educators can use to help couples preserve and protect their relationships during such a time. We describe four foundations of safety that allow relationships to thrive: physical, emotional, commitment, and community. We then highlight three keys from our body of work that can help guide individuals and couples in protecting their relationships on a day‐to‐day and moment‐to‐moment basis: (1) decide, don't slide; (2) make it safe to connect; (3) do your part. RESUMEN: La pandemia causada por el virus SARS‐CoV‐2 (coronavirus) y la enfermedad asociada, COVID‐19, ha causado un nivel de agitación mundial jamás visto en las vidas de la mayoría de las personas ahora vivas. Esta crisis afecta a las personas en sus relaciones más importantes, comprometidas e íntimas. Aunque esta crisis ha dañado la salud y el bienestar de las personas, destrozado las economías y llevado a un periodo extenso de incertidumbre acerca del futuro, también puede haber tenido consecuencias positivas en la motivación que tienen las personas para proteger sus relaciones. En este artículo, nos centramos en estrategias que los terapeutas y los capacitadores en relaciones pueden usar para ayudar a las parejas a preservar y proteger sus relaciones durante este tiempo. Describimos cuatro bases de seguridad que permiten que las relaciones prosperen: física, emocional, comprometida y comunitaria. Luego destacamos tres claves de nuestro trabajo que pueden contribuir a guiar a las personas y a las parejas a la hora de proteger sus relaciones día a día, momento a momento: 1) Decida, no haga cosas sin elegirlas 2) Encárguese de que sea seguro conectarse. 3) Haga su parte. 摘要: SARS‐CoV‐2病毒(冠状病毒)及其相关疾病COVID‐19造成的全球大流行，造成的严重动乱局面是目前大多数在世的人一生中从未见过的。这场危机影响着处于最重要的、忠诚度高的和亲密的关系中的人们。尽管这场危机有损个人的健康和福祉，摧毁了经济，并导致了一段对未来的广泛不确定时期，然而同时也在激励人们维护好他们的关系方面也可能产生了积极的结果。在本文中，我们关注的是在这样一个时期，治疗师和关系教育者可以用来帮助伴侣保持和维护他们关系的策略。我们描述了让关系茁壮成长的四个安全基础：身体方面的、情感方面的、承诺方面的和社区方面的。然后，我们在工作中强调三个关键，它们可以帮助指导个人和伴侣在日常以及每时每刻的基础上保护他们的关系: 1)做出决定，不要逃避；2)安全地连接；3)做好你的本分。